1983
DOI: 10.1104/pp.72.4.953
|View full text |Cite
|
Sign up to set email alerts
|

Membrane-Associated NAD-Dependent Isocitrate Dehydrogenase in Potato Mitochondria

Abstract: The oxidation isotherms for citrate and isocitrate by potato (Solanm tuberosum var. Russet Burbank) mitochondria in the presence of NAD differ markedly. Citrate oxidation shows positively cooperative kinetics with a sigmoid isotherm, whereas isocitrate oxidation shows MichaelisMenten kinetics at concentrations up to 3 millimolar, and cooperative kinetics thereafter up to 30 millimolar. In the absence of exogenous NAD, the isocitrate isotherm is sigmoid throughout. The dual isotherm for isocitrate oxidation in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
8
0

Year Published

1983
1983
2004
2004

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 17 publications
(15 reference statements)
2
8
0
Order By: Relevance
“…2 94,1990 The increase in the rate of isocitrate oxidation caused by NAD(P)+ is roughly the same at 3 and 10 mM isocitrate (Table V) while the background activity increases. For NAD+ this is consistent with previously reported results ( 15).…”
Section: Nadp Stimulates Malate and Isocitrate Oxidation By Intact MIsupporting
confidence: 83%
“…2 94,1990 The increase in the rate of isocitrate oxidation caused by NAD(P)+ is roughly the same at 3 and 10 mM isocitrate (Table V) while the background activity increases. For NAD+ this is consistent with previously reported results ( 15).…”
Section: Nadp Stimulates Malate and Isocitrate Oxidation By Intact MIsupporting
confidence: 83%
“…This has been noted in most studies on the enzyme from a number of sources (5,16,17,22). In an earlier study (7,8), it was suggested that citrate is a potent effector of the pea mitochondrial NAD+ ICDH.…”
Section: Discussionmentioning
confidence: 96%
“…The NAD+-specific ICDH has not been purified to homogeneity from a plant source, although some work has been done on the enzyme from peas (6-9, 11, 12) and potato (Solanum tuberosum) (17,20,21). Cox and Davies (7) man-Plant Physiol.…”
mentioning
confidence: 99%
“…NAD (12). Whereas tricarboxylic acid cycle dehydrogenases have most often been assigned to the matrix, Srere (24) and Matlib and O'Brien (15) have made a persuasive case for the association to varying degrees ofputative matrix enzymes to the inner membrane ofmammalian mitochondria.…”
mentioning
confidence: 99%
“…In the presence of exogenous NAD, potato mitochondria show a dual, or dromedary, ICDH isotherm (12 Mitochondria Preparation. Four hundred g of potato tubers were homogenized as described previously (10), except that the The inability of fresh potato slices to oxidize citrate (9), together with the known regulatory characteristics of NAD-linked isocitrate dehydrogenase (1,22), caused us to examine the behavior of ICDH4 in potato mitochondria from fresh slices.…”
mentioning
confidence: 99%